1965
DOI: 10.1136/bmj.2.5457.337
|View full text |Cite
|
Sign up to set email alerts
|

Use of Propranolol in Angina Pectoris

Abstract: Pronethalol, an adrenergic beta-receptor-blocking drug (Black and Stephenson, 1962), has been shown to relieve the pain of angina pectoris in a double-blind trial (Prichard, Dickinson, Alleyne, Hurst, Hill, Rosenheim, and Laurence, 1963). Its use in angina was, however, discontinued following a report of its tumour-producing activity in mice (Paget, 1963). A further disadvantage of pronethalol was that the therapeutic dose was close to that which produced side-effects.Black, Crowther, Shanks, Smith, and Dor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
0
1

Year Published

1966
1966
1996
1996

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(41 citation statements)
references
References 11 publications
2
38
0
1
Order By: Relevance
“…On balance, the beneficial effect of propranolol and other ,B-adrenoceptor blocking agents in anxiety would appear to be due to peripheral blockade rather than to central action. Thus, definite central effects of propranolol do occur in man (Gillam & Prichard, 1965;Stephen, 1966;Hinshelwood, 1969;Orzack, Branconnier & Gardos, 1973;Bryan, Efiong, Stewart-Jones & Turner, 1974) and in animals (Leszkovsky & Tardos, 1965; Bainbridge & Greenwood, 1971), but only in higher dosages than those used in the clinical studies of anxiety (Granville-Grossman & Turner, 1966;Wheatley, 1969). Practolol, a,-adrenoceptor blocking agent which does not enter the brain in appreciable amounts, is similar in effects to propranolol (Bonn, Turner & Hicks, 1972).…”
Section: Introductionmentioning
confidence: 99%
“…On balance, the beneficial effect of propranolol and other ,B-adrenoceptor blocking agents in anxiety would appear to be due to peripheral blockade rather than to central action. Thus, definite central effects of propranolol do occur in man (Gillam & Prichard, 1965;Stephen, 1966;Hinshelwood, 1969;Orzack, Branconnier & Gardos, 1973;Bryan, Efiong, Stewart-Jones & Turner, 1974) and in animals (Leszkovsky & Tardos, 1965; Bainbridge & Greenwood, 1971), but only in higher dosages than those used in the clinical studies of anxiety (Granville-Grossman & Turner, 1966;Wheatley, 1969). Practolol, a,-adrenoceptor blocking agent which does not enter the brain in appreciable amounts, is similar in effects to propranolol (Bonn, Turner & Hicks, 1972).…”
Section: Introductionmentioning
confidence: 99%
“…Die internistische Therapie blieb im wesentlichen auf zwei Entwicklungsstufen beschr~inkt, auf die Einftihrung der Nitrok6rper Ende des letzten Jahrhunderts durch Brunton (1867) sowie Murrell (1879) und Mitte der 60er Jahre dieses Jahrhunderts auf die Einfiihrung der Substanzen mit betasympathicolytischer Eigenschaft dutch Prichard (1965), Chaimberlain (1966), Sowton (1966 und zahlreiche andere Kardiologen (Lichtlen, 1970). Obwohl der therapeutische Effekt der internistischen Therapie, n~imlich die Verbesserung der Symptomatik, ftir diese Substanzen eindeufigbelegt ist, so ist die internistische Behandlung doch weit enffernt davon geblieben, kurativ zu sein.…”
Section: Schliisselw6rter: Angina Pectoris -Bypass-chirurgieunclassified
“…In more detailed studies it was found to be devoid of intrinsic sympathomimetic activity (Black, Duncan & Shanks, 1965;Shanks, 1966). Long term treatment with this agent was reported to cause reductions of blood pressure in hypertensive and normotensive patients (Prichard & Gillam, 1964;Gillam & Prichard, 1965). These authors attributed this effect of propranolol to interference with the function of the sympathetic nerves to the heart.…”
mentioning
confidence: 94%